Public policies focused on phytotherapy with emphasis on dentistry (Research, Society and Development, 2022)
It is known that public policies aimed at phytotherapy are expanding in Brazil. Several State and Municipal Health Departments have implemented Phytotherapy programs in primary health care, facilitating the population's access to medicinal plants and herbal medicines, filling drug shortages and improving the quality of life of disadvantaged communities. The discovery of plants with action in dentistry has aroused importance in the scientific community. Finding scientific evidence of the effect of these plants is of great importance for dentistry. Thus, the objective of this article is to carry out a survey in the literature of public policies aimed at phytotherapy with an emphasis on dentistry, health journals; specific articles on the subject, in Portuguese, English and Spanish, with the keywords: Public Policies, Phytotherapy and Dentistry. A review of national and international literature was carried out, including works between 2012 and 2022, publications indexed in SciFinder, BVS, Pubmed, SCIELO, Lilacs, Science Direct and Google academic. During the search, 52 articles were initially found, however, 38 articles were available in full. Articles that deal superficially with the theme were removed, leaving 30. From the analyzed studies, categories submerged: Public policies in phytotherapy; national policy on medicinal plants in dentistry; and the use of medicinal plants in Tocantins. It was observed that increasing the importance of public policies in phytotherapy in Brazil promotes public health and increases the promotion of the use of medicinal plants and herbal medicines. Thus, it is essential for health professionals, especially dentists, to know herbal indications against oral pathologies, strengthening their use by the public health system.